A 3D volume capture for ultrasound assessment of various organs and vessels by novice operators. (December 2022) - Arbeille, Philippe; Guillon, Laurent; Zuj, Kathryn; Besnard, Stephane; Clot, Christian
Abstract: Introduction: The quality of ultrasound images is dependent on operator skill level. Therefore, an automated system is required for situations, such as spaceflight, where a trained sonographer is not present. The current study compared an automated 3D volume capture method of ultrasound assessment (triggered by novices) with respect to teleoperation by sonographer expert (T-echo). Methods: Ultrasound images were collected from 14 participants (8 male) using a commercial portable echograph with motorized probes for volume capture (3D) and later teleoperated assessment (T-echo). A novice operator positioned the ultrasound probe over the acoustic window (AW) of interest using an AW body mapping with only confirmation of the placement by the distant sonographer, and held the probe stationary for both the 3D assessment and the teleoperated investigation. Results: There were no differences between the quality of T-echo and 3D images for the majority of structures assessed. Strong relationships were found between the measurements made with both methods (r values between 0.79 and 0.961) with an average difference less than 5% for all parameters measured. Conclusion: The automated 3D capture method acquired images with minimal effect on measurement values. While this 3D method may not be appropriate for structures that are moving during the volume capture (heart), it does present a functional method of acquiring ultrasound diagnostic images with a distant sonographer only verifying the positioning of the ultrasound probe on the AW. With software (under development) driving automatically the novice hand directly to the AW the 3D echography, will be fully automated. Highlights: The volumic video capture performed by a novice with later Expert 3D analysis allow to get organs diagnostic images.